THE EFFECT OF THE COLLABORATIVE LEARNING MODEL ON JUNIOR HIGH SCHOOL STUDENTS' MATHEMATICS PROBLEM-SOLVING ABILITIES - Mentari, Lidia (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
This study aims to determine the effect of the collaborative learning model on student problem-solving. Students were given a test to assess their mathematical problem-solving abilities, as well as their responses and activities related to the learning process. The researcher then described these results in data analysis. The method used was a pre-experimental method with a one-group pre-test, post-test design. This research was conducted at the SPF Technical Implementation Unit (UPTD) of SMP NEGERI 2 IPU BANYAK BARAT with 25 eighth-grade students. The results of the hypothesis test showed a calculated t-value of 16.4037, with a t-table value at the significance level of 0.5, which is 2.060. This means that the calculated t-value is greater than the t-table value, or 16.4037 > 2060. Therefore, Ha is accepted and H0 is rejected. It can be concluded that the collaborative learning model has a significant effect on the mathematical problem-solving abilities of students at UPTD SPF SMP NEGERI 2 IPU BANYAK BARAT.